Newborn Screening for X-Linked Adrenoleukodystrophy in Nebraska: Initial Experiences and Challenges - Craig V. Baker; Alyssa Cady Keller; Richard Lutz; Karen Eveans; Krystal Baumert; James C. DiPerna; William B. Rizzo (MDPI AG, 2022)
X-linked adrenoleukodystrophy (X-ALD) is a neurodegenerative disease caused by pathogenic variants in ABCD1 resulting in defective peroxisomal oxidation of very long-chain fatty acids. Most male patients develop adrenal insufficiency and one of two neurologic phenotypes: a rapidly progressive demyelinating disease in mid-childhood (childhood cerebral X-ALD, ccALD) or an adult-onset spastic paraparesis (adrenomyeloneuropathy, AMN). The neurodegenerative course of ccALD can be halted if patients are treated with hematopoietic stem cell transplantation at the earliest onset of white matter disease. Newborn screening for X-ALD can be accomplished by measuring C26:0-lysophosphatidylcholine in dried blood spots. In Nebraska, X-ALD newborn screening was instituted in July 2018. Over a period of 3.3 years, 82,920 newborns were screened with 13 positive infants detected (4 males, 9 females), giving a birth prevalence of 1:10,583 in males and 1:4510 in females. All positive newborns had DNA variants in ABCD1. Lack of genotype-phenotype correlations, absence of predictive biomarkers for ccALD or AMN, and a high proportion of ABCD1 variants of uncertain significance are unique challenges in counseling families. Surveillance testing for adrenal and neurologic disease in presymptomatic X-ALD males will improve survival and overall quality of life.